Avaliação experimental dos efeitos do anestésico local ropivacaína em nervos ciáticos - Zittlau, Mara Lúcia Costamilan; Taboga, Sebastião Roberto [UNESP] (My University, 2002)
This study was undertaken to investigate the effects of ropivacaine after intrafascicular injection into the sciatic nerves of albino rabbits. Twenty adult albine rabbits were used, following sedation with intramuscular ketamine (50 mg/kg) for nerve exposure by lateral incision. We considered three experimental groups: Group I:sciatic nerve control; Group II: intrafascicular injection with 0.2 mL of physiologic saline solution in the left nerves and intrafascicular injection with 0.2 mL of local anesthetic ropivacaine into the rigth nerves. The specimens were colected at 48 h after drugs administration; Group III. intrafascicular injection with 0.2 mL of physiologic saline solution in the left nerves and intrafascicular injection with 0.2 mL of local anesthetic ropivacaine in the rigth nerves. The specimens were colected at 7 days after drugs administration. The sciatic nerves were removed from these animals and fixed in Karnowisky solution for 24 hours. After partial dehydration up to 95% ethanol, they were embedded in historesin (Leica). The tissue was then sectioned at 1-2μm. Sections were stained with haematoxylin-eosin (HE); toluidine blue (TB) or picrosirius-haematoxylin (PSH). Comparing with control group the histological evidence of inflammatory reaction (migration of macrophagic cells and eosinophils-appeared soon after injection, with intense proliferation of perineurial cells. The results show that after 7 days of intrafascicular injection there was a severe fibrosis and an increase on perineurial vascularization. In group 2 the inflammatory reaction was noted near the local of the injection. Furthermore in this experiment we observed an increase on the number of epineurial lipoblasts and adipocytes. This study demonstrated that the toxic effects of ropivacaine are transient. In many cases there was an initial fascicular recover and axonal regeneration after 7 days of the injection.
Experimental evaluation of the local anesthetic ropivacaine effects on sciatic nerves
Keywords: Histology; Neurotoxicity; Ropivacaine; Sciatic nerve; alcohol; eosin; fixative; hematoxylin; ketamine; local anesthetic agent; resin; ropivacaine; sodium chloride; tolonium chloride; xylazine; adipocyte; animal experiment; animal model; animal tissue; cell proliferation; controlled study; drug administration route; drug effect; eosinophil; fibrosis; histology; inflammation; macrophage migration; nerve regeneration; neurotoxicity; nonhuman; perineurium; rabbit; sciatic nerve; sedation; vascularization